Carbohydrase inclusion in a corn-soybean diet improves broiler growth performance - Simões, Flávio Eduardo de Souza (2023)
An experiment was conducted to evaluate the effect of diets with reduced energy level content, supplemented with carbohydrase, on broiler performance and the coefficient of metabolizability of nutrients. A total of 720 one-day-old male Cobb-500 chicks were distributed in a completely randomized design, with six treatments, eight repetitions of 15 birds each. The treatments were: (1) a positive control, basal diet to meet the requirements of broiler chickens (PC); (2) a negative control, basal diet with a reduction of 80 kcal kg-1 (NC); (3) NC + alphagalactosydase; (4) NC + xylanase; (5) NC + xylanase and alphagalactosydase, and (6) NC + enzymatic blend (alphagalactosydase, xylanase, pectinase and amylase). The nutrient digestibility was not improved by use of enzymes. At 7 days of age, the broilers which were fed diets supplemented with enzymes showed a lower feed intake (FI) and better feed conversion ratio (FCR) than the broilers fed on PC.  Both the NC and enzymatic blend resulted in a worse performance of the broilers at 21, 35 and 42 days old. The use of alphagalactosydase and xylanase, isolated or in combination, in a corn-soybean meal-based diet is effective in improving the growth performance of broilers fed energy-reduced diets.